2007
DOI: 10.1212/01.wnl.0000269676.07319.09
|View full text |Cite
|
Sign up to set email alerts
|

Phase II/III randomized trial of TCH346 in patients with ALS

Abstract: The trial revealed no evidence of a beneficial effect of TCH346 on disease progression in patients with ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 26 publications
0
56
0
1
Order By: Relevance
“…Based on these positive preclinical results, omigapil was tested in clinical trials for Parkinson's disease and amyotro- jpet.aspetjournals.org phic lateral sclerosis. Although omigapil was shown to be safe, no significant difference in key outcome measures could be demonstrated between placebo-and omigapil-treated patients (Olanow et al, 2006;Miller et al, 2007), and the possible reasons for this failure were explored and discussed (Waldmeier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these positive preclinical results, omigapil was tested in clinical trials for Parkinson's disease and amyotro- jpet.aspetjournals.org phic lateral sclerosis. Although omigapil was shown to be safe, no significant difference in key outcome measures could be demonstrated between placebo-and omigapil-treated patients (Olanow et al, 2006;Miller et al, 2007), and the possible reasons for this failure were explored and discussed (Waldmeier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a phase III study of minocycline in ALS, a statistically significant trend toward faster progression in the ALS Functional Rating Scale-revised (ALSFRS-R) in patients treated with minocycline versus placebo; there was a trend in the same direction for MMT, but this was not significant [6]. A large, phase II trial of TCH346 in ALS showed a trend toward detriment on most outcome measures assessed but no effect on MMT [7]. Other studies have employed MMT testing in ALS, spinobulbar muscular atrophy, and spinal muscular atrophy (SMA) [8][9][10][11][12].…”
Section: Methods Of Strength Assessment Manual Muscle Testingmentioning
confidence: 99%
“…However, a neuroprotective effect in clinical trials involving PD and amyotrophic lateral sclerosis patients failed to show any beneficial effect during therapy (Olanow et al, 2006;Miller et al, 2007). Currently, Omigapil is under investigation in a study involving patients with congential muscular dystrophy.…”
Section: Fine-control and Specificity Of Gapdh As A Thiol Switch Gapdmentioning
confidence: 99%